2016
DOI: 10.1039/c5mb00547g
|View full text |Cite
|
Sign up to set email alerts
|

Strand-specific RNA-seq analysis of the Lactobacillus delbrueckii subsp. bulgaricus transcriptome

Abstract: Lactobacillus delbrueckii subsp. bulgaricus 2038 (Lb. bulgaricus 2038) is an industrial bacterium that is used as a starter for dairy products. We proposed several hypotheses concerning its industrial features previously. Here, we utilized RNA-seq to explore the transcriptome of Lb. bulgaricus 2038 from four different growth phases under whey conditions. The most abundantly expressed genes in the four stages were mainly involved in translation (for the logarithmic stage), glycolysis (for control/lag stages), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…Although Rickettsia genomes evolved by reductive evolution, 1–2% of the genes, either split or fragments, may still be active, thus corroborating previous studies that demonstrated transcription of several split/fragment genes in R. conorii (Ogata et al, 2001), Mycobacterium leprae (Akama et al, 2009) and Lactobacillus delbrueckii (Zheng et al, 2016). The expressed split genes were thought to conserve functional domains, or proposed to function as a class of non-coding RNAs and act as riboregulators at both the transcriptional and post-transcriptional levels (Erdmann et al, 2001; Zheng et al, 2016). However, the remaining altered genes were not expressed, suggesting that they may have lost their functions (i.e., by becoming pseudogenes).…”
Section: Discussionsupporting
confidence: 82%
“…Although Rickettsia genomes evolved by reductive evolution, 1–2% of the genes, either split or fragments, may still be active, thus corroborating previous studies that demonstrated transcription of several split/fragment genes in R. conorii (Ogata et al, 2001), Mycobacterium leprae (Akama et al, 2009) and Lactobacillus delbrueckii (Zheng et al, 2016). The expressed split genes were thought to conserve functional domains, or proposed to function as a class of non-coding RNAs and act as riboregulators at both the transcriptional and post-transcriptional levels (Erdmann et al, 2001; Zheng et al, 2016). However, the remaining altered genes were not expressed, suggesting that they may have lost their functions (i.e., by becoming pseudogenes).…”
Section: Discussionsupporting
confidence: 82%
“…RNA-seq studies are additionally informative, because they provide enhancement of the accuracy of existing genome annotations, for example in Bacillus anthracis [ 43 ]. A few RNA-seq studies have been recently described in Lactobacillus species [ 44–49 ]. The study by Zheng et al on Lactobacillus delbrueckii subsp.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with higher quantities of ManM in L. casei Zhang when cultured in soymilk ( 29 ) and increased transcripts for the glucose/mannose-specific PTS during L. delbrueckii subsp. bulgaricus 2038 incubation in whey ( 18 ). Taken together, these findings indicate that L. delbrueckii subsp.…”
Section: Discussionmentioning
confidence: 99%
“…The need for purine biosynthesis and salvage proteins in milk is supported by transcriptome analyses of L. delbrueckii subsp. bulgaricus 2038 and ATCC BAA-365 in whey and skim milk, respectively ( 4 , 18 ). The production of purine biosynthetic proteins was also elevated in other LAB (e.g., Lactobacillus helveticus , L. casei , and Lactococcus lactis ) when grown in milk ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation